Analisis Kinerja Keuangan Usaha Agrowisata Yoga Barista di Desa Singapadu, Kecamatan Sukawati, Kabupaten Gianyar - WIJAYA, I NYOMAN TRI ANANTA; SUAMBA, I KETUT; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018, 2018)
Financial Performance Analysis of Yoga Barista Agrotourism in Singapadu Village, Sukawati District, Gianyar Regency Agrotourism is one type of agribusiness business. All types of businesses need to make financial reports. Yoga Barista Agrotourism is located in Singapadu Village, Sukawati District, Gianyar Regency. This research discusses the financial performance of Yoga Barista Agrotourism using financial ratio analysis and discriminant analysis (Z-score), as well as the constraints faced during the five years period from 2012 until 2016. The constraints faced by Yoga Barista Agrotourism were discussed descriptive-qualitatively which included internal and external constraints. The results of this research were that the ratio analysis showed during the year 2012 until the year 2016, Yoga Barista Agrotourism has a good financial performance. Atlman Zscore model analysis showed that in 2012 the Yoga Barista Agrotourism was categorized into a gray area and 2013 until 2016 was categorized into healthy category.Constraints faced in running the Yoga Barista Agrotourism were internal constraints such as constraints of working hours and services and external constraints such as civet coffee product supply, land conversion and tourist visit season. Yoga Barista Agrotourism could improve financial performance and business health by improving management and improving business performance.